PENGARUH PROMOSI ONLINE,CELEBRITY ENDORSEMENT TERHADAP PERILAKU PEMBELIAN IMPULSIF BERDAMPAK PEMBELIAN ULANG DENGAN WORD OF MOUTH : THE EFFECT OF ONLINE PROMOTION, CELEBRITY ENDORSEMENT ON IMPULSIVE BUYING BEHAVIOR IMPACT OF REPURCHASING WITH WORD OF MOUTH - Maulina, Bella Yulinda; Derriawan Derriawan; Miranda, Agustinus (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study was to determine the effect of online promotion and celebrity endorsement on impulsive buying behavior that has an impact on repeat purchases with word of mouth (WOM) as a moderating variable. The population of this study are consumers who have shopped for clothing products on e-commerce (Shopee, Tokopedia, Bukalapak, Lazada, and Blibli). The number of samples from the population is 255 people who were taken using non-probability sampling technique. The statistical method used in this study is Structural Equation Modeling (SEM) which is operated through the SmartPLS program. In this study, it was found that online promotion variables had a significant effect on impulsive buying behavior which had an impact on repeat purchases, and the role of word of mouth played a significant role in moderating repeat purchases. Meanwhile, celebrity endorsement and impulse purchases has no significant effect on repeat purchases directly.